Общее понятие договора по законодательству Республики Казахстан - Мусина, К.А. (Изд-во КарГУ., 2009)
Мақалада келісім жасасу негізіндегі заңнамаларды шығару жəне тұжырымдамалық тарапының шарт жиынтығы келісім түсінігі анықталады. In the given article the concept of the agreement is defined as a set of conditions formulated by the parties and sounding in the legislation on which making of contract is based.